2022
DOI: 10.1039/d2nj01167k
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the photocatalytic efficiency of nanoscale TiO2 anatase with doped (Nd/Y) and co-doped (Nd–Y/Nd–Sm) lanthanides to decompose the azo dye orange G under UV-VIS irradiation

Abstract: Engineering a powerful visible light-driven organic dyes decomposition has been always considered a crucial challenge in the photocatalytic domain. Therefore, the high photocatalytic efficiency of Nd single doped and Nd/Y,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…In another notable work, Wang et al [43] synthesized Y and Eu co-doped TiO 2 nanoparticles through a sol-gel procedure and investigated their photocatalytic activities by monitoring the degradation of MB under UV light irradiation. Very recently, the high photocatalytic efficiency of Nd, Nd-Y, and Nd-Sm co-doped TiO 2 nanoparticle photocatalysts was confirmed by implementing the decomposition of azo dye Orange G [44]. The stability and recyclability of all photocatalysts used in this study were investigated, and it was found that the best stability was shown by Nd-Y co-doped TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 69%
“…In another notable work, Wang et al [43] synthesized Y and Eu co-doped TiO 2 nanoparticles through a sol-gel procedure and investigated their photocatalytic activities by monitoring the degradation of MB under UV light irradiation. Very recently, the high photocatalytic efficiency of Nd, Nd-Y, and Nd-Sm co-doped TiO 2 nanoparticle photocatalysts was confirmed by implementing the decomposition of azo dye Orange G [44]. The stability and recyclability of all photocatalysts used in this study were investigated, and it was found that the best stability was shown by Nd-Y co-doped TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 69%
“…Guetni et al found that doping TiO 2 with Nd allows the material to absorb radiation in the visible range by creating Nd-4f impurity states. The co-doping with Y further increases the Azo dye orange G degradation under a wavelength range of 300–800 nm due to the synergetic effect of intragap levels [ 63 ].…”
Section: Semiconductor Photocatalystsmentioning
confidence: 99%